Implementasi Metode Black Box pada Sistem Informasi Rekognisi Pembelajaran Lampau Berbasis Website - Fenty Kurnia Oktorina (Jurnal Sains dan Ilmu Terapan, 2025)
The RPL assessment process at Kampar Polytechnic is still done manually, so the data received by related parties is not well organised and difficult to store efficiently. This condition causes a lack of time efficiency and decreased work productivity. To overcome these problems, the solution offered is the development of a website-based information system. This system aims to simplify data collection, management, storage, and distribution, so as to produce more structured information and support online decision making. This research uses the Rapid Application Development (RAD) method with the Laravel framework in system development. The results showed that the past learning recognition information system has been well integrated. Based on the results of black box testing, the system achieved 100% success rate, which indicates that this system is capable and can improve the smoothness of the assessment process in RPL.